Do institutions have a greater effect on female entrepreneurs? - Saul Estrin; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2009)
This paper compares the impact of institutions on individual decisions to become entrepreneurs in the form of new business start ups by males and females across 44 developed and developing economies between 1998 and 2004. We test four hypotheses; that women are less likely to undertake entrepreneurial activity in countries where the rule of law is weaker; where the state sector is larger; where the informal financial sector is weaker and where the formal financial sector is weaker. We use data from the Global Enterprise Monitor survey (GEM) which covers at least 2,000 individuals annually in each of up to 44 countries, merged with country-level data, from the WB WDI and Heritage Foundation. We start with a spectrum of institutional variables and by utilizing factor analysis prior to regression estimation models, we are able to obtain results that are more robust and address multicollinearity between the institutional measures. We find that women are less likely to undertake entrepreneurial activity in countries where the state sector is larger, and demonstrate that this result applies to both high aspiration and low aspiration entrepreneurship. We also find that women benefit more from the larger informal financial sector.
Keywords: L26; J16; H11; O16; O17; P43; 330; Female entrepreneurship; state sector; informal finance; Weibliche Führungskräfte; Unternehmer; Unternehmensgründung; Institutionalismus; Staatsquote; Informeller Finanzsektor; Welt